Competency of School Administrators in the Digital Age Affecting the Learning Organization under the Phetchaburi Primary Educational Service Area Office 2 - Yaemtad, Duanghathai; Boonsong, Kanchana (Ratchaphruek Journal, 2025)
This research aimed to study: 1) The competency of administrators in the digital age; 2) The learning organization in schools; and 3) The competency of administrators in the digital age affecting the learning organization of schools. The sample used in this research consisted of 269 teachers under the Phetchaburi Primary Educational Service Area Office 2, selected through a multi-stage sampling method. The research instrument was a 5-point Likert scale questionnaire. The statistical methods used for data analysis were percentage, mean, standard deviation, and stepwise multiple regression analysis. The research findings revealed that: 1) The competency of administrators in the digital age, was generally at a high level; 2) The learning organization in schools, was generally at a high level; and 3) The competency components of administrators in the digital age affecting the learning organization of schools under the Phetchaburi Primary Educational Service Area Office 2 included teamwork), change management, technology literacy, and self-development which effectively predicted 77.00%.